The unutilized potential of temporary use of space: A case study of Avtomatik Delovišče, Koper - Tina Cotič; Matjaž Uršič (Urbani Izziv)

(untitled)
Degraded, underutilized, or abandoned spaces are a formidable challenge and an unused opportunity for many contemporary cities. In such cases, temporary use of space has proved to be an efficient spatial practice, allowing the best use of spatial resources of a particular place and time. During the last two decades, temporary use of space has become the subject of much debate and unambiguous praise in academic circles, primarily validated as a socially progressive, economical, and flexible spatial practice that may initiate an innovative, new, and inclusive culture of urban life. It is considered a catalyst for change that, using experimental solutions, can relatively quickly revive degraded spaces while at the same time preserving their individual, historical, and environmental qualities. This article verifies theoretical approaches to the temporary use of space with the results of a participatory case study of Avtomatik Delovišče in the Slovenian city of Koper. The study focuses on the effects of the spatial practice applied in the urban environment and, consequentially, its potential role in urban regeneration. With the help of a multiple case study of temporary uses in various cities in Slovenia, the main goal is to determine the extent to which alternative, experimental, and temporary spatial interventions can contribute to increased urban diversity, community involvement, creativity, innovation, and local identity. Furthermore, the article examines the ways in which temporary use is perceived and accepted by the residents, professional community, and official representatives of the City Municipality of Koper.